2015
DOI: 10.1007/s11104-015-2764-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity hotspots and Ocbil theory

Abstract: Background Ocbil theory aims to develop hypotheses explaining the evolution and ecology of, and best conservation practices for, biota on very old, climatically buffered, infertile landscapes (Ocbils). Scope This paper reviews recent multi-disciplinary literature inspired by or reacting to aspects of Ocbil theory and discusses how it can assist conservation in biodiversity hotspots. Conclusions Ocbils occur in at least 12 out of 35 known terrestrial hotspots, but also in other biologically significant sites. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
129
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 362 publications
(437 reference statements)
13
129
1
1
Order By: Relevance
“…Ultimately, extreme longevity combined with the genetic consequences of wide outcrossing as a result of bird pollination are likely to be important for the persistence of genetic variation in small, geographically isolated stands of E. caesia. This conclusion is in accordance with the James Effect Hypothesis (Hopper, 2009;Hopper et al, 2016) that predicts that mechanisms conserving heterozygosity will feature prominently in rare, localised endemics, as a result of prolonged genetic isolation.…”
Section: Discussionsupporting
confidence: 88%
“…Ultimately, extreme longevity combined with the genetic consequences of wide outcrossing as a result of bird pollination are likely to be important for the persistence of genetic variation in small, geographically isolated stands of E. caesia. This conclusion is in accordance with the James Effect Hypothesis (Hopper, 2009;Hopper et al, 2016) that predicts that mechanisms conserving heterozygosity will feature prominently in rare, localised endemics, as a result of prolonged genetic isolation.…”
Section: Discussionsupporting
confidence: 88%
“…High levels of endemism can result from two scenarios: either (a) these environments promote high local speciation (neoendemisms), or (b) they permit survival of lineages that undergo extinction elsewhere (palaeoendemisms) (Keppel et al, ). Even though campo rupestre have been classified as an old, climatically buffered and infertile landscape (Conceição et al, ; Hopper, Silveira, & Fiedler, ), thus intuitively associating them to palaeoendemisms, phylogenies of some endemic lineages have shown that recent, fast speciation is surprisingly common (e.g., Antonelli, Verola, Parisod, & Gustafsson, ; Ribeiro, Rapini, Damascena, & Berg, ; Rando et al, ). There is certainly scope for further investigation on this question and we strongly believe that officializing these bioregions is going to facilitate such studies.…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptus caesia Benth., a long‐lived bird‐pollinated lignotuberous tree endemic on granite outcrops, is a well‐suited species to study patterns of genetic structure and connectivity of historically fragmented populations at a landscape scale (Bezemer et al, ; Byrne & Hopper, ; Moran & Hopper, ). Our study is located in the Southwest Australian Floristic Region (Hopper & Gioia, ), a global biodiversity hot spot with numerous examples of old, climatically buffered infertile landscapes (OCBILs) and, consequently, old plant lineages with complex evolutionary histories (Hopper, ; Hopper, Silveira, & Fiedler, ). Eucalyptus caesia populations have a scattered distribution in south‐western Australia with 25 known stands ranging in size from a single individual to several hundred plants based on aerial and on‐ground surveys (Hopper, Campbell, & Moran, ; present paper).…”
Section: Introductionmentioning
confidence: 99%